Extensive sequence analysis of CFTR, SCNN1A, SCNN1B, SCNN1G and SERPINA1 suggests an oligogenic basis for cystic fibrosis-like phenotypes - Ramos, M.D.; Trujillano, D.; Olivar, R.; Sotillo, F.; Ossowski, S.; Manzanares, J.; Costa, J.; Gartner, S.; Oliva, C.; Quintana, E.; Gonzalez, M.I.; Vazquez, C.; et al. (Clinical genetics, 2014)
The term cystic fibrosis (CF)‐like disease is used to describe patients with a borderline sweat test and suggestive CF clinical features but without two CFTR(cystic fibrosis transmembrane conductance regulator) mutations. We have performed the extensive molecular analysis of four candidate genes (SCNN1A, SCNN1B, SCNN1G and SERPINA1) in a cohort of 10 uncharacterized patients with CF and CF‐like disease. We have used whole‐exome sequencing to characterize mutations in the CFTR gene and these four candidate genes. CFTR molecular analysis allowed a complete characterization of three of four CF patients. Candidate variants in SCNN1A, SCNN1B, SCNN1G and SERPINA1 in six patients with CF‐like phenotypes were confirmed by Sanger sequencing and were further supported by in silico predictive analysis, pedigree studies, sweat test in other family members, and analysis in CF patients and healthy subjects. Our results suggest that CF‐like disease probably results from complex genotypes in several genes in an oligogenic form, with rare variants interacting with environmental factors.